PRAKTIK PEMBERIAN MAKANAN PENDAMPING ASI (MP-ASI) SEBAGAI FAKTOR RISIKO KEJADIAN STUNTING PADA ANAK USIA 6-23 BULAN DI KECAMATAN SEDAYU, KABUPATEN BANTUL, DAERAH ISTIMEWA YOGYAKARTA - , HILDAGARDIS M.E. NAI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Stunting reflects a process of failure to reach linear growth potential as a result of suboptimal health or nutrition conditions. Children will become stunted if they do not receive an adequate quantity and quality of complementary foods after six months of age. The objective of the study was to identify age introduction of complementarary foods, dietary diversity, and meal frequency as a risk factors of stunting among children aged 6-23 months. Methods: The study used both quantitative methods as well as case control design and qualitative through interview. The study population was children aged 6-23 months in Sedayu Subdistrict from February to April 2014. Cases were selected with total sampling methods with total cases were 126 children. Case-control ratio was 1:1. Subject consisted of 252 children of 6-23 months. Data were analyzed by using univariable (descriptive), bivariable (chi-square test), and multivariable analysis (multiple logistic regression). Result: The result of bivariable analysis showed that age introduction of complementary foods (OR=1,07